The role of representative motor games in physical education in the development of the motor compatibility of primary school students from the faculty’s point of view. - difallah, imed; benamar, djebbouri; bouaziz, mohamed (sports creativity, 2024)
This study investigates how representative motor games can contribute to the development of motor skills in primary school students, as perceived by physical education teachers. A random sample of 30 teachers received a questionnaire, and statistical analysis using SPSS showed that representative motor games enhance coordination, balance, and basic motor skills in students. The study recommends the inclusion of motor exercises based on representative motor games in educational programs for primary schools.